EFFECT OF REPLACEMENT COMMERCIAL RATION WITH FERMENTED GREEN BEAN SPROUT WASTE FLOUR ON THE MEAT ORGANOLEPTIC OF EIGHT WEEKS OLD MALE BALI DUCK - E. D., Karisma; Puger, A. W.; Siti, N. W. (Jurnal Peternakan Tropika, 2020)
Waste of mung bean sprouts is a part of mung bean sprouts that are not utilized in the production process, even usually wasted. This study aims to determine the effect of replacing commercial rations with fermented mung bean sprouts flour on meat organoleptic of eight weeks old male bali duck. The study used a completely randomized design (CRD) with three treatments, each treatment using five replications and each replication used three male bali ducks with weight of 43,8±0.96g. The treatment given were; P0 (100% commercial ration), P1 (replacement 12.5% of commercial ration with fermented mung bean sprout waste flour) and P2 (replacement of 25% commercial ration with fermented mung bean sprout waste flour). Organoleptic testing uses a hedonic test (preference test) with 16 semi-trained panelists with variables observed in this study are color, texture, aroma, taste, and overall assessment. The results showed that the replacement up to 25% of commercial rations with fermented mung bean sprouts flour affected highly  significant (P<0.05) on organoleptic color, texture, aroma, taste, and overall assessment with a preference value of 25% replacement was 4.06 (like to very like), replacing 12.5% fermented mung bean flour skin with a preference value  3.13 (ordinary to like) and the lowest value in the control treatment with a preference value 2.5  (dislike to ordinary). Based on the results of the study it can be concluded that the replacement of commercial rations with fermented mung bean sprouts flour up to 25% can increase the panelists' preference for organoleptic male bali duck meat at eight weeks age. Key words : Male bali ducks, fermented mung bean sprout flour, organoleptic, commercial                    rations.